Gender inequality: The challenge of contemporary demography - Šobot Ankica (Sociologija, 2010)
Gender perspective is a heuristic device in researching social phenomena, and gender inequality is a social fact which requires an adequate answer. Also, social differences between women and men are examined as relevant factors of demographic phenomena. The contemporary demography is opening up space not only for the gender aspect, but also for gender inequality as a relevant research topic. This paper discusses the possibilities of demographic approach to studying social inequality between women and men. By analyzing socio-demographic structures and their dynamics insight is obtained into the generality, tendencies and particular features of the phenomenon. This is the specifically demographic contribution to understanding gender inequality.